Complex regulatory element within the gammaE- and gammaF-crystallin enhancers mediates Pax6 regulation and is required for induction by retinoic acid - Králová, Jarmila; Czerny, Thomas; Spanielová, Hana; Ratajová, Veronika; Kozmik, Zbynek (Gene, 2002)
The paired domain, DNA-binding domain of Pax6 and other Pax transcription factors, is composed of two subdomains (PAI and RED), each recognizing distinct half-sites of the bipartite binding site in adjacent major grooves of the DNA helix. The alternatively spliced Pax6(5a) isoform containing 14 extra amino acids within the PAI domain recognizes the 5aCON sequence consisting of four interdigitated 5' half-sites of the bipartite consensus sequence. A genome database search for similar tetrameric Pax6(A) recognition sequences led to the identification of a Pax6-binding site in the lens-specific enhancer of the mouse E- and F-crystallin genes. This binding site combines the properties of bipartite and tetrameric recognition sequences and, by mutational analysis, is shown to mediate Pax6-dependent regulation of the E- and F-crystallin promoter constructs both in primary chicken lens cells and in chicken embryo fibroblasts. The Pax6-binding site is adjacent to a previously identified retinoic acid response element and is itself required for retinoic acid induction of the F- and E-crystallin genes, suggesting that Pax proteins and retinoic acid receptors cooperate in transcriptional regulation. In summary, our protein-DNA binding and transactivation studies suggest that -crystallin genes are under the control of a multifunctional enhancer element that mediates Pax6 regulation as well as retinoic acid-mediated induction.
Keywords: Regulatory Sequences, Nucleic Acid; DNA-Binding Proteins; receptory kyseliny retinové; sekvence nukleotidů; Luciferases; regulační oblasti nukleových kyselin; Basic Helix-Loop-Helix Transcription Factors; Promoter Regions, Genetic; Recombinant Fusion Proteins; DNA vazebné proteiny; regulace genové exprese; Down-Regulation; Transcription Factors; sekvenční homologie nukleových kyselin; retinoidní X receptory; Paired Box Transcription Factors; zesilovače transkripce; epitelové buňky; vazebná místa; Lens, Crystalline; plazmidy; zvířata; Homeodomain Proteins; Cells, Cultured; represorové proteiny; PAX6 Transcription Factor; Binding Sites; down regulace; kuřecí embryo; Chick Embryo; transfekce; Repressor Proteins; Epithelial Cells; Gene Expression Regulation; Crystallins; Base Sequence; luciferasy; kultivované buňky; oční proteiny; homeodoménové proteiny; Sequence Homology, Nucleic Acid; Eye Proteins; rekombinantní fúzní proteiny; Enhancer Elements, Genetic; krystaliny; transkripční faktory bHLH; Transfection; transkripční faktory; Animals; Retinoid X Receptors; Tretinoin; transkripční faktory paired box; Plasmids; Receptors, Retinoic Acid; oční čočka; promotorové oblasti (genetika); tretinoin; transkripční faktor PAX6